For the new commentary on "Canti leopardiani" by Luigi Blasucci (Prassi Ecdotiche della Modernità Letteraria, 2019)
The text is the reproduction of the lecture held in Milan, at the Braidense National Library, during the presentation of Giacomo Leopardi, Canti, a cura di Luigi Blasucci, Parma, Fondazione Pietro Bembo - Ugo Guanda Editore, 2019, vol. I, pp. LXXXI-470.
Keywords: Canti; Giacomo Leopardi; Luigi Blasucci; commented edition; commentary